Perancangan Perbaikan Proses Produksi Komponen Bodi Mobil Daihatsu dengan Lean Manufacturing di PT. “XYZ” - Satria Khalif Isnain; Putu Dana Karningsih (Trunojoyo University of Madura, 2018)
Astra Daihatsu Motor Company. Potential market for automotive is continuously growing which is positive signal for automotive businesses. However nowadays competition is also getting stronger. Therefore PT Inti Pantja Press Industri should efficiently manage their production. One way is by reducing and eliminating waste in its production. Production process in PT. Inti Pantja Press Industri is still having several problems. Based on early observation there are bottleneck in subassy processes and also defective product. Reffering to these problems, it can be indicated that there are several waste in production process of PT. Inti Pantja Press Industri.Therefore, Lean Manufacturing approach is utilized to reduce or eliminate waste in production processes. First, various waste are identified using Value Stream Mapping. Borda Count Method is used for determining critical waste that occur, they are as follow: waste waiting, defect, and overproduction that cause over inventory finish product. Then, 5 Whys Analysis specifies root causes of waste waiting and waste defect. By using Failure Mode and Effect Analysis, highest priority of root causescan be selected, which are operator do not clean dies before press process, operator do not replace components that has already over its lifetime (wear) and rust on finish product part. Recommendations for improvements are conducted by implementating Poka Yoke method, they are: installation of sensors and equipment in Press machines and wrapping finish part product.